Epigenetic methylation status of P16, MGMT and SPOCK2 in diffuse Large B cell lymphoma - Mohd. Ridah, Lailatul Jalilah; Ismail, Aziah; A. Talib, Norlelawati; Muhammad, Siti Aeshah @ Naznin; Hussain, Faezahtul Arbaiyah; Zainuddin, Norafiza (IIUM, 2016)
Introduction: Epigenetic methylation has been implicated in the pathogenesis of diffuse large B cell lymphoma (DLBCL). This study investigated the methylation status of p16, MGMT and SPOCK2. Aberrantly methylated p16 and MGMT have been linked to DLBCL, but not SPOCK2. p16 inhibits cyclin-dependent kinase, which results in retinoblastoma phosphorylation and blockage of cell cycle at G1 phase. MGMT removes alkyl adduct at O6-guanine, thus preventing lethal cross-links. SPOCK2, an extracellular chondroitin and heparin sulfate proteoglycans, abolishes the inhibition of membrane-type 1-matrix metalloproteinase which might enhance the angiogenesis. The absence of SPOCK2 methylation was therefore hypothesized in the majority of cases in this study. Methods: Extracted DNA from 88 formalin-fixed paraffin-embedded (FFPE) tissues of DLBCL were subjected to bisulfite conversion followed by methylation-specific PCR (MSP) analysis for p16, MGMT and SPOCK2 methylation. p16 methylation was also quantified in 16 samples through pyrosequencing assay. Results: p16 methylation was observed in 65/88 (74%) samples by MSP. Pyrosequencing detected p16 methylation in all 16 samples ranging from 18% to 81%. MGMT methylation was detected in all 88 (100%) cases. Methylated SPOCK2 was found in 83 (94.3%) samples. There was a significant association between p16 methylation status with patients above 50 years of age (p= 0.04). Conclusions: These preliminary discoveries may serve as a good platform in order to gain a comprehensive overview on the epigenetics contribution in the pathogenesis of DLBCL. Pyrosequencing is a robust tool in detecting and quantifying methylation.